Efficacy of mirror therapy in improving hand function post flexor tendon repair - Bayoum, Mohamed Bayoumi Ibrahim; Nagy Saleh , Ahmed Mohamed; Saafan, Karim Ibrahim; Elsayeh, Shaimaa Mohamed Ahmed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to determine the efficacy of mirror therapy (MT) in improving the total active range of motion (AROM) of the affected finger, hand grip strength, and hand function in patients with flexor tendon repair (FTR) in zone II. The study was an open-label, parallel-group, randomized controlled trial. Thirty patients with zone II FTR, aged 20-45 years, were recruited and randomized into two equal groups: the MT group and the sham MT group. The intervention began in the fourth week post-operation, consisting of thirty minutes of MT or sham MT, three sessions per week for four weeks, in addition to the traditional physical therapy (PT) program. The total AROM of the interphalangeal (IP) joints of the affected fingers, hand grip strength, and hand function were assessed. After four weeks of intervention, the percentage change in total AROM was 25.7% in the MT group and 19.93% in the sham MT group. Additionally, hand grip strength and Michigan Hand Outcomes Questionnaire (MHQ) scores showed greater improvement in the MT group compared to the sham MT group (p < 0.05). Adding MT to the traditional PT program may be more effective than the traditional PT program alone in improving the AROM of the interphalangeal (IP) joints of the operated fingers, grip strength, and MHQ scores.